Prognostic nutritional index as a novel marker for prediction of prognosis in patients with peripartum cardiomyopathy - Tak, Bahar Tekin (Medicine (Baltimore), 2020)
The clinical significance of poor nutritional status in patients with peripartum cardiomyopathy (PPCM) is not clearly understood. Prognostic nutritional index (PNI) is a simple nutritional assessment tool, which was first demonstrated to be valuable in patients with colorectal surgeries. We aimed to investigate the predictive value of PNI in patients with PPCM. A total of 92 patients diagnosed with PPCM were enrolled in this study. PNI was calculated using the following formula: 10 × serum albumin value (g/dL) + 0.005 × total lymphocyte count. The primary endpoint was defined as composite adverse cardiac events that included cardiac death or hospitalization due to worsening heart failure (HF). Cardiac death, hospitalization due to worsening HF, and persistent left ventricular (LV) systolic dysfunction were evaluated, respectively, as secondary endpoints. Primary composite endpoint was higher in the lower PNI group. After adjusting for other risk factors, PNI was found to be as an independent predictor of primary composite endpoint (odds ratio 0.805; 95% confidence interval 0.729–0.888; P < .001). In addition, PNI was significantly associated with secondary endpoints; persistent LV systolic dysfunction as well as cardiac death. This study identified nutritional status assessed by the PNI seems to be a novel predictor of adverse cardiovascular outcomes in patients with PPCM.